Music and the silent film : contexts and case studies, 1895-1924 - Marks, Martin Miller (OUP E-Books., 1997)
Most people's view of silent film music is of a pianist playing old scores while watching the flickering screen. This title shows that there was much more to silent films and that often it was planned from the start as an integral part of the film. The author argues that film scores are a major and vibrant part of 20th century music.